PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMESTURNAMENT(TGT) UNTUK MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR PADA KOMPETENSI KELISTRIKAN BODI SISWA KELAS XI OTOMOTIFSMK NAWA BAKTI KEBUMEN 2015/2016 - Imam Khanif Mustofa; Subagyo Subagyo (Jurnal Taman Vokasi, 2016)
The Application of Cooperative Learning Model Teams Games Tournament (TGT) To Increase Activity and Learning Outcomes of the Competence Electrical Body grade XI Automotive Students at SMK NawaBaktiKebumen. Mechanical Engineering Study Program thesis, Faculty of Teachers Training and Education SarjanawiyataTamansiswa University Yogyakarta, 2015.The aim of the research was to find out the type of cooperative learning methods TGT able to enhance students' learning activities and learning outcomes of the Competence Electrical Body grade XI Automotive Students at SMK NawaBaktiKebumen. The type of this research is a classroom action research (PTK) with 2 cycles. Each cycle consists of four stages: planning, action, observation, and reflection. The subject of the research were the XI grade students of NawaBakti which consists of 30 students. The data obtained was analyzed qualitatively. The data collection techniques observation and tests. The data were analyzed through qualitative descriptive technique.The result of this study indicate that the use of methods of cooperative TGT type can improve student learning activity from the pre-cycle students who pay attention and respond with enthusiasm what was conveyed by the teacher in learning activity 53%, while the percentage of students who brave to express opinions 33%, brave to respond to what is conveyed by peers 30% and seriousness in the evaluation step is only 60%. Addressing positive response was still low. In the first cycle, students who pay attention and respond enthusiastically what is conveyed by the teacher in learning activity 60%, while the percentage of students who brave to express opinions 36.67%, brave to respond to what is conveyed by peers 33.33% and seriousness in the evaluation step only 66.67%. Addressing a positive response is well developed. Whereas for the second cycle, students who pay attention and respond enthusiastically what is conveyed by the teacher in learning activity 73.33%, the percentage of students who brave to express opinions 43.33%, brave to respond to what is conveyed by peers 40% and seriousness in the evaluation step 73.33%. Percentage of the activity increase properly so the application activity through TGT model has been successful.Â Besides the activity increased, the application activity through TGT model able to improve learning outcomes that can be seen from the good result in each cycle, namely: on pre-cycle student learning classical result is 41% or students who pass the study were 12 students of 30 students, while in the first cycle of student learning outcomes in classical result is 56.67% or students who pass the study as many as 17 students of 30 students, and the second cycle showed that student learning outcomes as many as 25 students of 30 students have been pass the study in classical learning result is 83.33%.